Genetic characterization of amino acid and N-acetylglucosamine utilization in Aspergillus nidulans - Forster, Heather Dawn (My University, 2025)
Nutrient acquisition is an essential and controlled process in all living organisms. In the model fungus Aspergillus nidulans, the transcription factor AreA regulates nitrogen utilization genes. The areA102 pleiotropic altered function mutant shows increased growth on histidine as a nitrogen source, which is suppressed by the suppressor of areA102 mutants sarA and sarB. The sarA gene (AN2350) encodes an Lamino acid oxidase (LAAO), but sarB has remained unidentified. Whole genome sequencing led to identification of AN8875 as a sarB candidate. By complementing the sarB7 mutant phenotype on histidine with a wild-type AN8875 gene and phenocopying the areA102 sarB7 mutant phenotype on histidine in an areA102 AN8875Δ mutant, we conclusively showed that sarB is AN8875. sarB encodes a putative uridine diphosphate (UDP)-N-acetylglucosamine (UDPGlcNAc) transporter that is conserved in fungi and animals. The SarB protein is likely localized to the ER or Golgi. Through generation of a sarBΔ sarAΔ double mutant, we confirmed that sarB and sarA are in the same genetic pathway. Using in-gel and spectrophotometric LAAO assays on cell-free protein extracts we demonstrated that SarA LAAO activity was greatly reduced in areA102 sarBΔ mutants compared to the areA102 parent strain. SarA activity was increased and activity of a second putative LAAO, AN1808, was detected at a later timepoint. Through treatment of growing mycelia with tunicamycin, we found evidence that SarA is N-glycosylated and that N-glycosylation is necessary for full SarA activity. However, deletion of genes involved in N-glycosylation (N-acetylglucosamine transferase, GNT) and O-GlcNAcylation (O-GlcNAc transferase, OGT) did not phenocopy sarBΔ and sarAΔ mutants on histidine. Deletion of the GNT-encoding gene altered the electrophoretic mobility of SarA LAAO activity, suggesting a lack of GlcNAc decoration on N-glycans attached to SarA in the GNT mutant. Using RNA-seq analysis, we determined that sarA is upregulated on non-repressing nitrogen conditions and that sarB shows constitutive expression. Neither gene is regulated by the AreA co-repressor nmrA. The Ndt80-like transcription factor XprG plays important roles in regulation of nutrient acquisition, including catabolism of GlcNAc. Extracellular GlcNAc is imported by the GlcNAc transporter NgtA (AN1427), phosphorylated by the hexokinase HxkC (AN4255) to GlcNAc-6-phosphate, deacetylated by DacA (AN1428) to glucosamine-6phosphate, and deaminated by DamA (AN1418) to ammonium and fructose-6phosphate, which can enter nitrogen and carbon metabolism, respectively. We confirmed the necessity of XprG in utilization of GlcNAc as a nitrogen source and identified a putative GlcNAc sensor and histone deacetylase, NgsA (AN1416). We identified a second GlcNAc transporter in A. nidulans, NgtB (AN8127) that, when deleted, caused slightly reduced growth on GlcNAc as a nitrogen or carbon source. Simultaneous deletion of ngtA and ngtB was lethal. We showed that the GlcNAc utilization regulatory genes xprG and ngsA exhibit genetic interaction in GlcNAc catabolism and extracellular protease activity. RNA-seq experiments provided evidence that GlcNAc utilization is regulated by nitrogen metabolite repression and nmrA. Overall, our work shows that GlcNAc has multiple roles in nutrient acquisition in A. nidulans and suggests that its recycling may be essential for hyphal growth.
Keywords: Aspergillus nidulans; L-amino acid oxidase; Nitrogen metabolism; N-acetylglucosamine; Fungal genetics; Amino acids